THE LEVEL OF SANITARY-HYGIENIC WELL-BEING AS THE INDICATOR OF FUNCTIONAL CHANGES OF THE ORGANISM OF YOUNG SPORTSMEN - Skyba, O.А.; Pshenychna, L.V. (World of Medicine and Biology, 2017)
The dependence of the indicators of the functional state of the organism of young athletes on the level of sanitary and hygienic well-being of children's and youth sports schools has been determined. The most important sanitary and hygienic factors exerted on the indicators of the functional state of the children of the main (children, who engaged in institutions with an average level of sanitary and hygienic well-being) and the first control group (children, who engaged in institutions with a low level of sanitary and hygienic well-being).
Keywords: sanitary and hygienic factors; functional state of the organism; sports pathology